2012
DOI: 10.1016/j.rse.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Satellite microwave remote sensing for environmental modeling of mosquito population dynamics

Abstract: Environmental variability has important influences on mosquito life cycles and understanding the spatial and temporal patterns of mosquito populations is critical for mosquito control and vector-borne disease prevention. Meteorological data used for model-based predictions of mosquito abundance and life cycle dynamics are typically acquired from ground-based weather stations; however, data availability and completeness are often limited by sparse networks and resource availability. In contrast, environmental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 47 publications
(52 reference statements)
3
39
0
1
Order By: Relevance
“…This multifactor index was found to be a better early warning indicator for the onset of human WNV disease than predictions based on single sources of information [35]. Previous research in South Dakota has found influences of climatic variability on the abundance of vector mosquitoes [15,17] and human disease cases [18] and we suggest that combining these types of environmental indicators with mosquito and human case surveillance data offers a strong potential for improving our ability to predict the spatial and temporal dimensions of WNV in South Dakota as well as in other regions where WNV is endemic.…”
Section: Discussionmentioning
confidence: 99%
“…This multifactor index was found to be a better early warning indicator for the onset of human WNV disease than predictions based on single sources of information [35]. Previous research in South Dakota has found influences of climatic variability on the abundance of vector mosquitoes [15,17] and human disease cases [18] and we suggest that combining these types of environmental indicators with mosquito and human case surveillance data offers a strong potential for improving our ability to predict the spatial and temporal dimensions of WNV in South Dakota as well as in other regions where WNV is endemic.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy in temperature measurements is important for applying integrated pest management (IPM) in both forest and agricultural settings (e.g., Fand et al, 2014;Faye et al, 2014), for exploring the possible effects of global warming on ecosystems and organisms (e.g., Logan et al, 2004;Gutierrez et al, 2009;Ponti et al, 2009) and for developing strategies for the management of vector-borne diseases of humans and animals over large geographic areas (e.g., Rogers et al, 1996;Gilioli and Mariani, 2011;Amek et al, 2012;Chen and Hsieh, 2012). Recently, land surface temperature (LST) data derived from satellites have been proposed as a possible source of temperature data to be fed into insect population models and used to explore ecological and environmental questions (Carbajal de la Fuente et al, 2009;Coops et al, 2009;Chuang et al, 2012;Lensky and Dayan, 2011;Morag et al, 2012;Steinman et al, 2012;Blum et al, 2013;Aharonson-Raz et al, 2014). Lensky and Dayan (2011) used LST data to investigate the variability in the developmental rate of an agricultural pest (Heliothis sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Microwave radiometers onboard Earth observing satellites have been widely used for observing critical land surface parameters supporting environmental monitoring and global change studies [1][2][3][4]. High-quality and consistent geophysical retrievals from well-calibrated, stable radiometer observations and long-term data records are essential for accurately delineating regional patterns and distinguishing natural climate variations from more subtle environmental trends.…”
Section: Introductionmentioning
confidence: 99%